2014
DOI: 10.1021/am501617a
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Differential Electrochemical Stripping Behaviors of Fe3O4Nanocrystals toward Heavy Metal Ions by Crystal Cutting

Abstract: This study attempts to understand the intrinsic impact of different morphologies of nanocrystals on their electrochemical stripping behaviors toward heavy metal ions. Two differently shaped Fe3O4 nanocrystals, i.e., (100)-bound cubic and (111)-bound octahedral, have been synthesized for the experiments. Electrochemical results indicate that Fe3O4 nanocrystals with different shapes show different stripping behaviors toward heavy metal ions. Octahedral Fe3O4 nanocrystals show better electrochemical sensing perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 63 publications
(66 reference statements)
1
30
0
Order By: Relevance
“…Currently, anodic stripping voltammetry has been popularly applied to detect heavy metal ions in water owing to its high sensitivity, accurateness, and low cost [4][5][6][7]. To obtain high sensitivity and selectivity, nanostructured metal oxides have been widely employed as modifiers of the working electrodes [8][9][10][11]. The detection strategy stems from the selective adsorption properties of modifiers [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, anodic stripping voltammetry has been popularly applied to detect heavy metal ions in water owing to its high sensitivity, accurateness, and low cost [4][5][6][7]. To obtain high sensitivity and selectivity, nanostructured metal oxides have been widely employed as modifiers of the working electrodes [8][9][10][11]. The detection strategy stems from the selective adsorption properties of modifiers [12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, crystal plane effects have gained great interest in lots of fields, such as photocatalysts [19][20], solar cell [21,22], electrochemical energy storage [23,24], and so on. However, to the best of our knowledge, only a few studies have been focused on the facet-dependent electrochemical performances toward heavy metal ions detection [7,9,[25][26][27]. For instance, Xin-jiu Huang research group found that Cu2O microcrystals with different facets showed different sensitivity in the determination of lead ions, following the sequence (111) > (100) > (110) [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 As an important magnetic nanomaterial, Fe 3 O 4 magnetic nanoparticle received much attention and extensive investigation in the past years for its excellent electrocatalytic activity, biocompatibility and absorption ability. [19][20][21][22][23] For example, a sensitive electrochemical biosensor for the detection of H 2 O 2 from living cells has been developed based on graphene blended with Fe 3 O 4 nanoparticles. 24 Fe 3 O 4 nanosphere decorated with Au nanoparticles was used as a kind of catalyst for the detection of As(III) in water.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide coated glassy carbon electrode has also been demonstrated for ultrasensitive detection of heavy metals including Zn II ,C d II ,C u II ,H g II ,a nd Pb II ions. [18,19] Other research attributed the electrochemical performance of Fe 2 O 3 in the detection of Pb ion to be dependent on the facet of the Fe 2 O 3 nanostructure, particularly the facets {012}, {001}, and {110} of the nanocube, nanorod, and nanoplates structures. [20] Further studies focusedo ns ynthesizing Fe 2 O 3 with these effectivef acets exposed for the demonstration of detection of As III .…”
Section: Introductionmentioning
confidence: 99%